2017
DOI: 10.1097/bpo.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Version and Tibial Torsion are Not Associated With Hip or Knee Arthritis in a Large Osteological Collection

Abstract: These results support the practice of treating tibial torsion and femoral anteversion based on the symptomatology of the patient. Parents of asymptomatic children can be reassured that long-term consequences are unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 53 publications
(60 reference statements)
3
14
1
Order By: Relevance
“…Arthritis grading was performed by two authors (DSW, RWL) and has previously been reported. 15 , 16 These two individuals carefully studied a large number of specimens together to establish grading systems for the hip and knee joints. Arthritis of the proximal femur and acetabulum were graded from zero to three and combined to form a composite hip measurement, graded zero to six.…”
Section: Methodsmentioning
confidence: 99%
“…Arthritis grading was performed by two authors (DSW, RWL) and has previously been reported. 15 , 16 These two individuals carefully studied a large number of specimens together to establish grading systems for the hip and knee joints. Arthritis of the proximal femur and acetabulum were graded from zero to three and combined to form a composite hip measurement, graded zero to six.…”
Section: Methodsmentioning
confidence: 99%
“…8,9 A spine grading system was modified, 10 and a previously validated grading system for the hip and knee was used. 11 Spine osteoarthritis was evaluated with a scale from 0 to 4 at each vertebral joint level, from L1 to L2 through L5 to S1. Measurements from each level were averaged to represent a composite spine arthritis measurement, graded from 0 to 4.…”
Section: Arthritis Gradingmentioning
confidence: 99%
“…17 A proximal reference line parallel to a tangent line drawn at the anterior articular cartilage edge of the medial and the lateral tibial plateau has been described, 55 but due to the need to clearly observe local anatomic features, this application is limited to dry bone studies. 9,51 The 2 most clinically applicable methods we identified from previously proposed methods were the posterior tangent to the tibial condyles proximally 31,34,39 and the axis through a manually selected slice in the proximal tibia that has the widest transverse condylar diameter. 16 Limitations regarding both of these have been discussed above, specifically the challenges of clearly identifying proximal tibial morphology to apply the former method and of selecting the correct slice level and landmarks manually in the latter method.…”
Section: Discussionmentioning
confidence: 99%